Methodological Features of Improving the Teaching Methodology of Vertebrate Zoology in Higher Education Institutions (Eurasian Journal of Learning and Academic Teaching, 2023)
This article pays special attention to the methodology of teaching biology. The article presents opinions and comments on the goals and tasks of vertebrate zoology. In addition, the opinions of scientists on the methodology of teaching vertebrate zoology were expressed.